KEPADATAN, BIOMASSA, DAN POLA DISTRIBUSI KEONG LOLA (Trochus niloticus) DI PULAU SAPARUA, KABUPATEN MALUKU TENGAH - Handy Erwin Pier Leimena; Tati. S. Subahar; Adianto Adianto (The East Java Biological Society, 2007)
Lola (Trochus niloticus) is one of the largest size sea snail that live in coral reef at Indo Pacific region and Indonesia including Saparua Island. In a few recent years, lola population in Saparua Island tends to decline due to its exploitation for industrial need. This work aimed to estimate the density, biomass, and sistribution pattern of lola snail population in Saparua Island, Central Molluccas. Transects strip method was applied to collect the snail samples. Each transect was 100 meters long and two meters wide, which were divided into ten segments (10 m × 2 m), and laid perpendicular to the coast line started from the lowest tide level to the open sea. This study showed that average density of lola snail in Saparua Island is 620 individu/ha, with total biomass is 4.15 ton/ha. In Nolloth, lola snail have the highest density as well as the biomass, whilst in Ullath it shows the lowest density. The further down from the lowest tide level, the larger its shell diameter, and this relation can be expressed by y = –2.118 + 0.053x (r2 = 0.879). Morisita dispersion index revealed that the distribution pattern of lola snail is clumped.